Comparison of projected water availability and demand reveals future hotspots of water stress in the Red River basin, USA - Hamed Zamani Sabzi; Hernan A. Moreno; Rachel Fovargue; Xianwu Xue; Yang Hong; Thomas M. Neeson (Journal of Hydrology: Regional Studies, 2019)
Study region: Red River Basin of the South, United States of America. Study focus: We investigated the projected changes in water availability and demand across the Red River to identify regions of potential future water stress. The VIC model was calibrated, validated and then run with ensemble forcing from regionally representative global circulation model (GCM) outputs. For different combinations of representative concentration pathways (RCPs) we evaluated the impacts of climate change on streamflows and water availability throughout the basin. To estimate future water demand, we integrated a series of sector-specific regression models fit to historical water usage per county. New hydrological insights for the region: Despite discrepancies among GCMs projections, all future scenarios include a strong west-east gradient in water availability. Joint consideration of projected water demand and availability reveals that the distribution of future hotspots of water stress is spatially patchy and generally driven by changes in water demand, rather than availability. These hotspots of future water stress highlight locations of potential water conflicts. Our approach is likely to be applicable to drought-prone river basins worldwide where the spatial patterns of future water availability differ from spatial patterns of future water demand. Keywords: Drought, U.S. Southern Plains, Climate change impacts, Water use, Environmental conservation planning, Watershed management